2020
DOI: 10.1152/ajpheart.00434.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors are associated with immune cell mitochondrial respiration in humans

Abstract: Modifiable cardiometabolic risk factors induce the release of pro-inflammatory cytokines and reactive oxygen species from circulating peripheral blood mononuclear cells (PBMCs) resulting in increased cardiovascular disease risk and compromised immune health. These changes may be driven by metabolic reprogramming of PBMCs resulting in impaired mitochondrial respiration; however, this has not been fully tested. We aimed to determine the independent associations between cardiometabolic risk factors, such as blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…These suggestions are mainly derived from a small number of studies, showing that post-endurance-exercise protein ingestion may increase myofibrillar synthesis and/or activators of mitochondrial biogenesis such as peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) [ 54 , 55 , 56 ]. Given that mitochondrial function and capacity are closely related to CRF [ 57 ] and cardiometabolic health [ 58 , 59 ], the potential beneficial impact of post-exercise protein ingestion on maximizing the training-related adaptations of the mitochondria, as detected in previous studies, is encouraging. However, it has also been pointed out that the evidence of the role of protein supplementation on endurance-training adaptations is still rather inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…These suggestions are mainly derived from a small number of studies, showing that post-endurance-exercise protein ingestion may increase myofibrillar synthesis and/or activators of mitochondrial biogenesis such as peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) [ 54 , 55 , 56 ]. Given that mitochondrial function and capacity are closely related to CRF [ 57 ] and cardiometabolic health [ 58 , 59 ], the potential beneficial impact of post-exercise protein ingestion on maximizing the training-related adaptations of the mitochondria, as detected in previous studies, is encouraging. However, it has also been pointed out that the evidence of the role of protein supplementation on endurance-training adaptations is still rather inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, is has been suggested that the link between cardiometabolic risk factors and altered immune cell function is via reduced respiratory capacity, and a recent study did show this in apparently healthy individuals with some risk markers—hinting at immune cell reprogramming towards glycolysis [ 234 ]. Platelets can also be used to measure mitochondrial function, are easier to isolate than PBMCs, and they do seem to reflect overall systemic mitochondrial function; initial studies in runners before and after an event do seem to support this [ 144 , 235 ].…”
Section: Discussionmentioning
confidence: 99%
“…A standardized XF assay protocol ensures reliable and comparable results across different PBMC donors, which increases the applicability of human PBMCs in experimental studies. Over the past decade, several clinical studies tested the applicability of metabolic PBMC responses as marker in the context of multiple disease pathologies such as diabetes 19 , 20 , 34 , 54 , 55 , cardiovascular disease 35 , 56 , obesity 21 , inherited metabolic diseases 22 , 57 , neurodegenerative diseases 23 , 58 , autoimmune disease 24 and schizophrenia 59 , as well as in the context of altered physiological conditions such as pregnancy 25 or responses to changed micronutrient status 33 . Future use of brightfield image analysis in such studies will standardize the XF assay workflow and improve data interpretation and comparison across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of XF assay results is critical for accurate and consistent data interpretation and comparison. Multiple parameters for XF assay data normalization in PBMCs have been used, of which normalization to the number of plated cells via pre-XF assay cell counting has been mostly applied 20 , 21 , 24 , 33 35 . However, cell number and cell layer distribution are affected by daily and operator variation in counting, plating and handling, which can lead to inaccurate normalization.…”
Section: Introductionmentioning
confidence: 99%